Identifikasi Pewarna Sintesis pada Produk Olahan Bunga Rosella (Hibiscus sabdariffa) dengan Metode Kromatografi Lapis Tipis - Rezqi Handayani; Henilisa Yuliyana Larasati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Food additives are often used or added intentionally into processed food or beverage products are dyes. Dyes are divided into two types: natural dyes and synthetic dyes. Syrup circulating in the community generally contains a lot of synthetic dyes, this is done by manufacturers to reduce production costs and make the appearance of materials to be attractive. The use of synthetic dyes in addition to having a positive impact on producers and consumers can also cause a negative impact, especially for consumers. When compared with natural dyes, synthetic dyes have the more negative impact on health. Currently, farmer groups from Kalampangan Village treat Rosella as syrup. Evident from the observations in the field Rosella syrup production of farmers groups is quite interested in the local community. Therefore this study aims to analyze synthetic dyes on Rosella processed products produced by farmer groups from Kalampangan Urban Village, Palangka Raya. Rosella flower syrup samples were analyzed qualitatively by Thin Layer Chromatography (TLC) method. In the Thin Layer Chromatography method, the sampling treatment was carried out by the withdrawal of the dye using a fat-free wool yarn. There are 4 (four) synthetic dyes identified by the identification in the sample Ponceau, Carmoisine, Brilliant Blue and Rhodamine B. The result obtained is on Eluen I (Ethyl Methyl Ketone: Acetone: Water) Rf raw Ponceau 4R 0.7667, Rf raw Carmoisine 0.8266, Rf Brilliant Blue 0.7466 raw, and Rf raw Rhodamin B 0.8667 while in the sample there is no stain.